Krisis Autentisitas dalam Komunikasi Digital: Tantangan AI-Generated Content terhadap Kepercayaan Publik di Era Post-Authenticity - Mochammad Naufal (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The development of Generative Artificial Intelligence (Generative AI) has transformed digital communication through its ability to generate increasingly realistic text, images, audio, and video. While this technology enhances information production efficiency, it also raises serious challenges regarding authenticity, credibility, and public trust. However, studies that integrate AI-generated content, authenticity, hyperreality, and public trust remain limited. This study aims to analyze the impact of AI-generated content on digital communication authenticity and its implications for public trust in the post-authenticity era. A qualitative approach is employed using a Conceptual Literature Review, drawing on Baudrillard’s theory of hyperreality and Goffman’s dramaturgical perspective as the main analytical frameworks. The findings indicate that AI-generated content expands digital simulation spaces, blurring the boundaries between reality and representation. Phenomena such as deepfakes, voice cloning, and virtual influencers reinforce hyperreality conditions, making authenticity increasingly difficult to verify. This situation contributes to rising misinformation, declining public trust, and a shift in information legitimacy from factual truth to perceived authenticity. This study proposes the concept of post-authenticity communication as a framework for understanding the transformation of digital communication in the era of generative AI. The findings emphasize the importance of digital literacy, AI transparency, and content verification systems in maintaining public trust.